Development of a High-Frequency Test System to Study the Wear of Ultrasonic Welding Tools - Junqi Li; Michael Rienks; Frank Balle (Metals, 2023)
In current automotive lithium-ion battery manufacturing, Ultrasonic Metal Welding (USMW) is one of the major joining techniques due to its advantages in welding multiple thin sheets of highly conductive materials. The sonotrode, serving as the welding tool, transmits high-frequency oscillation to the joining parts. Due to the high frequency of thermal-mechanical loading, the knurl pattern on the sonotrode wears with an increasing number of welds, which significantly influences the welding process, resulting in poor joint quality. In this study, a high-frequency test system was developed to investigate the wear mechanisms of the sonotrode. Based on the comparable relative motion to the welding process, the thermal-mechanical loadings on the contact area were analyzed. As the oscillation amplitude of the sonotrode increased, the estimated frictional force between the sonotrode and the copper counter body remained constant, while an increase in the sliding distance was observed in the contact area. Temperature development showed a strong correlation with mechanical loading. A first approach of continuous testing was performed but was limited due to the failure of the copper counter body under ultrasonic stimulation.